Dimethyl fumarate as a safe and effective therapy for recalcitrant psoriasis in comorbid patients - Martina Burlando; Mattia Fabio Molle; Emanuele Cozzani; Aurora Parodi (PAGEPress Publications, 2021)
Psoriasis is a chronic condition for which multiple therapies are currently available. In particular, in cases of moderate-severe psoriasis, traditional systemic drugs or the new biological drugs can be administered. However, the treatment of patients who require systemic therapy and have multiple comorbidities can be particularly complex. Some treatment options may be in fact contraindicated or may lose effectiveness over time, reducing the options available to the dermatologists. In such circumstances, dimethyl fumarate may represent a safe and effective choice, also in patients who have already attempted biological therapies. In this regard, we report the case of a patient with moderatesevere psoriasis treated over time with various therapies (including topicals, phototherapy, traditional and biological drugs) that were discontinued due to ineffectiveness or incompatibility caused by the occurrence of concomitant diseases, who finally achieved clinical remission with dimethyl fumarate.